Forty minutes to glory : inside the Kentucky Wildcats' 1978 championship season - Brunk, Doug (University Press of Kentucky, 2018)
"Winning a national title ... winning it at Kentucky? There's nothing like it. You're always going to be remembered."--Truman Claytor, member of UK's 1977--1978 NCAA National Championship team Joe B. Hall, Jack "Goose" Givens, Rick Robey, and Kyle Macy -- these names occupy a place of honor in Rupp Arena, home of the "greatest tradition in the history of college basketball." The team and coaches who led the University of Kentucky Wildcats to their 94--88 victory over the Duke Blue Devils in the 1978 national championship game are legendary. Yet the full, behind-the-scenes story of this team's incredible redemptive season has remained untold until now. In Forty Minutes to Glory, Doug Brunk presents an inside account of this celebrated squad and their championship season from summer pick-up games to the net-cutting ceremony in St. Louis. Brunk interviewed every surviving player, coach, and student manager from the 1977--1978 team and he shares unbelievable tales, such as how James Lee's father talked him out of quitting. Brunk also reveals heart-wrenching moments, recounting the time when Jay Shidler traveled 150 miles to visit his seriously ill mother on the eve of the national semifinals game against Arkansas and how Scott Courts coped with his father's death just days before the championship game against Duke. Published to coincide with the fortieth anniversary of the national championship victory, Forty Minutes to Glory invites the Big Blue Nation to relive a special season. Featuring chapters by Jack Givens and Coach Hall, this engaging book is a fitting tribute to one of the most talented and determined teams ever to compete on the hardwood